Students making videos on social media: exploring the potential of online videos for language learning (Texto Livre, 2024)
In recent years, communication on social media has undergone major changes, shifting towards being more multimodal and video-centred. This study investigates the engagement of Portuguese university students in video production within social media platforms and examines their perceptions of language learning opportunities inherent to this practice. We conducted a questionnaire among 212 students at the University of Aveiro (Portugal), delving into the role of video-making as an interactive learning tool. Our results show that roughly 22% of the respondents make videos, indicating that video production is not very common among them, especially when compared to video watching. Despite this, our analysis highlights several possible educational benefits of making online videos. Our data illustrate the interactive and multilingual nature of online video-making, encompassing practices such as searching for information, collaborating with others, or watching other similar videos in different languages. Finally, while this study highlights the infrequency of video production, it underscores its potential as a holistic approach to language learning and the development of multiliteracies.